Contextual cues about reciprocity impact ratings of smile sincerity. Issue 6 (18th August 2022) - Gagnon, Mathieu; Chérif, Lobna; Roy-Charland, Annie
ABSTRACT: Research has shown that context influences how sincere a smile appears to observers. That said, most studies on this topic have focused exclusively on situational cues (e.g. smiling while at a party versus smiling during a job interview) and few have examined other elements of context. One important element concerns any knowledge an observer might have about the smiler as an individual (e.g. their habitual behaviours, traits or attitudes). In this manuscript, we present three experiments that explored the influence of such knowledge on ratings of smile sincerity. In Experiments 1 and 2, participants rated the sincerity of Duchenne and non-Duchenne smiles after having been exposed to cues about the smiler's tendency to reciprocate (this person always, never or occasionally returns favours). In Experiment 3 they performed the same task but with cues about the smiler's love of learning (this person always, never or occasionally enjoys learning new tasks). The results show that cues about the smiler's reciprocity tendency influenced participants' ratings of smile sincerity and did so in a stronger manner than cues about the smiler's love of learning. Overall, these results both strengthen and broaden the literature on the role of context on judgements of smile sincerity.